Pengaruh Pendidikan Kesehatan Berbasis Website Terhadap Penurunan Tingkat Kecemasan Pada Pasien Pra Pemasangan Catheter Double Lumen (CDL) - Alya Bhatari, Nabila; Ciptaning Tyas, Maria Diah; Supono, Supono; Marsaid (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: This study aims to determine the effect of website-based health education on reducing anxiety levels in pre-treatment patients with CDL. Methods: This research is a quasy experimental type with a two-group pre-test-post test design. The sample consisted of 36 respondents who were selected using pur-posive sampling. Data analysis used the Wilcoxon test and the Mann-Whitney test. Before being given the website-based intervention, most respondents expe-rienced moderate levels of anxiety. Results: After the intervention, most respondents experienced mild levels of anxiety. Wilcoxon test analysis showed p-value = 0.000 and Mann-Whitney test analysis for anxiety levels after intervention showed p-value = 0.023. Conclusion: The conclusion is there is an influence of website-based health education on reducing patient anx-iety levels before CDL installation.